Asymptomatic Plasmodium infections in 18 villages of southern Savannakhet Province, Lao PDR (Laos). - Phommasone, K; Adhikari, B; Henriques, G; Pongvongsa, T; Phongmany, P; von Seidlein, L; White, N; Day, N; Dondorp, A; Newton, P; Imwong, M; Mayxay, M (Malaria Journal, 2016)
Background A large fraction of Plasmodium infections do not cause clinical signs and symptoms of disease and persist at densities in blood that are not detectable by microscopy or rapid diagnostic tests. These infections may be critical as a transmission reservoir in areas of low malaria endemicity. Understanding the epidemiology of these infections would be helpful for malaria elimination. Methods A cross-sectional survey was conducted in Thapangthong and Nong Districts of Savannakhet Province, Lao PDR, to determine the prevalence of parasitaemia. A total of 888 blood samples were collected from afebrile volunteers aged ≥15 years in 18 villages during March and July 2015. Plasmodiuminfections were diagnosed by rapid diagnostic tests (RDT) and high volume, ultra-sensitive quantitative polymerase chain reaction (uPCR). Results uPCR detected Plasmodium infections in 175 of 888 samples (20 %). The species distribution was Plasmodium falciparum 3.6 % (32/888), Plasmodium vivax 11.1 % (99/888), mixed infections with P. falciparum and P. vivax 1.6 % (14/888) and Plasmodium of undetermined species 3.4 % (30/888). RDT identified only 2 % (18/888) positive cases. Using uPCR as reference, the sensitivity and specificity of RDTs were 28 and 100 %, respectively, in detecting P. falciparum infections, and 3 and 99 % in detecting asymptomatic P. vivax infections. The K13 kelch propeller domain C580Y mutation, associated with reduced susceptibility to artemisinin derivatives, was found in 75 % (12/18) of P. falciparum isolates from Thapangthong and in 7 % (2/28) from Nong (p < 0.001). In a multivariate analysis, males were more likely to have P. vivaxinfections [adjusted odds ratio (aOR) 4.76 (95 % CI 2.84–8.00)] while older villagers were at lower risk for parasitaemia [aOR for increasing age 0.98 (95 % CI 0.96–0.99)]. Conclusion There is a high prevalence of asymptomatic Plasmodium infections in southern Savannakhet. Artemisinin-resistant P. falciparum strains form an increasing proportion of the parasite population in Thapangthong District and are already present in the more remote Nong District. This worrying trend has wider implications for Laos and could reverse the gains achieved by the successful control of malaria in Laos and the Greater Mekong Sub-region (GMS). Rapid elimination of P. falciparum has to be a top priority in Laos as well as in the wider GMS.